CHITINASE LIKE1 Regulates Root Development of Dark-Grown Seedlings by Modulating Ethylene Biosynthesis in Arabidopsis thaliana - Gu, Shin-Yuan; Wang, Long-Chi; Cheuh, Chiao-Mei; Lo, Wan-Sheng (Frontiers in Plant Science, 2019)
The plant hormone ethylene plays a regulatory role in development in light- and dark-grown seedlings. We previously isolated a group of small-molecule compounds with a quinazolinone backbone, which were named acsinones (for ACC synthase inhibitor quinazolinones), that act as uncompetitive inhibitors of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS). Thus, the triple response phenotype, which consists of shortened hypocotyls and roots, radial swelling of hypocotyls and exaggerated curvature of apical hooks, was suppressed by acsinones in dark-grown (etiolated) ethylene overproducer (eto) seedlings. Here, we describe our isolation and characterization of an Arabidopsis revert to eto1 9 (ret9) mutant, which showed reduced sensitivity to acsinones in etiolated eto1 seedlings. Map-based cloning of RET9 revealed an amino acid substitution in CHITINASE LIKE1 (CTL1), which is required for cell wall biogenesis and stress resistance in Arabidopsis. Etiolated seedlings of ctl1ret9 showed short hypocotyls and roots, which were augmented in combination with eto1-4. Consistently, ctl1ret9 seedlings showed enhanced sensitivity to exogenous ACC to suppress primary root elongation as compared with the wild type. After introducing ctl1ret9 to mutants completely insensitive to ethylene, genetic analysis indicated that an intact ethylene response pathway is essential for the alterations in root and apical hook but not hypocotyl in etiolated ctl1ret9 seedlings. Furthermore, a mild yet significantly increased ethylene level in ctl1 mutants was related to elevated mRNA level and activity of ACC oxidase (ACO). Moreover, genes associated with ethylene biosynthesis (ACO1 and ACO2) and response (ERF1 and EDF1) were upregulated in etiolated ctl1ret9 seedlings. By characterizing a new recessive allele of CTL1, we reveal that CTL1 negatively regulates ACO activity and the ethylene response, which thus contributes to understanding a role for ethylene in root elongation in response to perturbed cell wall integrity.